2020
DOI: 10.1007/s12602-020-09656-5
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Administration Increases Amino Acid Absorption from Plant Protein: a Placebo-Controlled, Randomized, Double-Blind, Multicenter, Crossover Study

Abstract: The fate of dietary protein in the gut is determined by microbial and host digestion and utilization. Fermentation of proteins generates bioactive molecules that have wide-ranging health effects on the host. The type of protein can affect amino acid absorption, with animal proteins generally being more efficiently absorbed compared with plant proteins. In contrast to animal proteins, most plant proteins, such as pea protein, are incomplete proteins. Pea protein is low in methionine and contains lower amounts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(111 citation statements)
references
References 28 publications
4
107
0
Order By: Relevance
“…They showed that nuts, beans, insects, fish or protein powders (from pea, soy or whey) provided the highest efficiency with the least EnvI, while beef, cheese, and some processed refined grains (such as rice or egg pasta) were the least efficient and had the highest EnvI. However, the list of products and serving sizes analyzed in the current study was not extensive enough (due to the lack of availability of some data) and we did not analyze the combination of different protein sources (animal with plant-based combinations) or culinary techniques that could complement or increase amino acid availability of plant-based sources [ 88 , 89 , 90 ]. In athletes, only limited research has integrated DIAAS of plant-based diets.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that nuts, beans, insects, fish or protein powders (from pea, soy or whey) provided the highest efficiency with the least EnvI, while beef, cheese, and some processed refined grains (such as rice or egg pasta) were the least efficient and had the highest EnvI. However, the list of products and serving sizes analyzed in the current study was not extensive enough (due to the lack of availability of some data) and we did not analyze the combination of different protein sources (animal with plant-based combinations) or culinary techniques that could complement or increase amino acid availability of plant-based sources [ 88 , 89 , 90 ]. In athletes, only limited research has integrated DIAAS of plant-based diets.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics can also limit pathogen adhesion to host tissue, and modulate the production of different metabolites such as vitamins, short-chain fatty acids, and molecules that act as neurotransmitters involved in gut-brain communication [4]. Beyond benefiting physiological systems, probiotics have been shown to impact the absorption and production of key nutrients, including minerals, carbohydrates, protein, cholesterol, and various forms of digestive enzymes [5][6][7].…”
Section: Open Accessmentioning
confidence: 99%
“…Therefore, there is an interest in nutritional strategies to raise the blood amino acid concentrations after ingesting a plant protein source to overcome compositional shortcomings. To assess the amino acid concentration in the blood after the administration of a plant protein with or without coadministration of a probiotic supplement (5 × 10 9 CFU Lactobacillus paracasei LP-DG and 5 × 10 9 L. paracasei LPC-S01) a randomized, double-blind, crossover pilot study was performed in physically active males [ 20 ▪▪ ]. Probiotic administration significantly increased methionine (+16.3%), histidine (+49.2%), valine (+24.7%), leucine (+25.2%), isoleucine (+26.1%), tyrosine (+11.6%), total BCAA (+26.8%), and total essential amino acid (+15.6%) maximum concentrations and area under the curve (Fig.…”
Section: Introductionmentioning
confidence: 99%